Evidências de validade fatorial e precisão da escala de atitudes em saúde mental - SOUSA, Patrícia Fonseca de; MACIEL, Silvana Carneiro; TORRES, Ana Raquel Rosas; LIMA, Tiago Jessé Souza de; MEDEIROS, Katruccy Tenório; VIEIRA, Giselli Lucy Souza (Estudos de Psicologia (Campinas), 2023)
This study gathered evidence of factorial validity and internal consistency of the Attitudes in Mental Health Scale. Two studies were performed. A total of 404 college students, including women (69.6%) with a mean age of 24 years (Standard Deviation = 5.67), participated in Study 1. A total of 396 college students, including females (69.9%) with a mean age of 23 years (Standard Deviation = 5.41), participated in Study 2. In the first study, an exploratory factorial analysis indicated the existence of two factors (biomedical paradigm, á = 0.71; psychosocial paradigm, á = 0.66) with a total of 15 items. In the second study, a confirmatory factorial analysis indicated that the bifactorial model that was proposed for the scale was adequate: ÷²/df = 2.41, GFI = 0.93 and RMSEA = 0.06, 90%IC [0.05 - 0.07]. The results concluded that this measure can be adequately applied in studies in the proposed measurement context.